Post-Newtonian Approximation of Teleparallel Gravity Coupled with a Scalar Field - Zu-Cheng, Chen; Wu, You; Hao, Wei (arXiv.org, 2015)
We use the parameterized post-Newtonian (PPN) formalism to explore the weak field approximation of teleparallel gravity non-minimally coupling to a scalar field \(φ\), with arbitrary coupling function \(ω(φ)\) and potential \(V(φ)\). We find that all the PPN parameters are identical to general relativity (GR), which makes this class of theories compatible with the Solar System experiments. This feature also makes the theories quite different from the scalar-tensor theories, which might be subject to stringent constraints on the parameter space, or need some screening mechanisms to pass the Solar System experimental constraints.